(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study assessed the accessibility of library services for persons with disabilities in selected federal universities in Nigeria. The study was motivated by the need to determine the extent to which university libraries provide inclusive services, facilities, information resources, and assistive technologies that support equitable access to information for persons with disabilities. Specifically, the study sought to identify the library services available to persons with disabilities, determine the accessibility of library facilities and information resources, and examine the assistive technologies and support services provided in federal university libraries. A descriptive survey research design was adopted, using a quantitative approach. The study covered six federal universities representing the six geopolitical zones of Nigeria: Ahmadu Bello University, University of Maiduguri, University of Ilorin, University of Ibadan, University of Nigeria, Nsukka, and University of Port Harcourt. The population of the study comprised 1,000 registered persons with disabilities, from which a sample size of 286 respondents was drawn using proportionate and purposive sampling techniques. Data were collected through a structured questionnaire, and 282 valid responses were analyzed using descriptive statistics, including frequencies, percentages, means, and standard deviations. The findings revealed that most conventional library services, including reference services, circulation services, internet and ICT services, online database access, and reprographic services, were available to persons with disabilities. The study further found that library facilities and information resources were moderately accessible, with electronic resources, digital databases, library entrances, and catalogues recording relatively high accessibility levels. The study concluded that although federal university libraries in Nigeria have made notable efforts toward improving accessibility, significant gaps still exist in the provision of disability-focused services and assistive technologies. The study recommends increased investment in accessible infrastructure, specialized assistive technologies, staff training, and inclusive library policies to enhance equitable access to library services for persons with disabilities.